The applications and techniques of organoids in head and neck cancer therapy - Qi, Hao; Tan, Xiaolin; Zhang, Wenshuo; Zhou, Yihong; Chen, Shaoyi; Zha, Dasong; Wang, Siyang; Wen, Jinming (Frontiers in Oncology, 2023)
Head and neck cancer (HNC) is one of the most common cancers on the planet, with approximately 600,000 new cases diagnosed and 300,000 deaths every year. Research into the biological basis of HNC has advanced slowly over the past decades, which has made it difficult to develop new, more effective treatments. The patient-derived organoids (PDOs) are made from patient tumor cells, resembling the features of their tumors, which are high-fidelity models for studying cancer biology and designing new precision medicine therapies. In recent years, considerable effort has been focused on improving “organoids” technologies and identifying tumor-specific medicine using head and neck samples and a variety of organoids. A review of improved techniques and conclusions reported in publications describing the application of these techniques to HNC organoids is presented here. Additionally, we discuss the potential application of organoids in head and neck cancer research as well as the limitations associated with these models. As a result of the integration of organoid models into future precision medicine research and therapeutic profiling programs, the use of organoids will be extremely significant in the future.